2015
DOI: 10.1096/fj.14-260844
|View full text |Cite
|
Sign up to set email alerts
|

SHP2 regulates osteoclastogenesis by promoting preosteoclast fusion

Abstract: Genes that regulate osteoclast (OC) development and function in both physiologic and disease conditions remain incompletely understood. Shp2 (the Src homology-2 domain containing protein tyrosine phosphatase 2), a ubiquitously expressed cytoplasmic protein tyrosine phosphatase, is implicated in regulating M-CSF and receptor activator of nuclear factor-κB ligand (RANKL)-evoked signaling; its role in osteoclastogenesis and bone homeostasis, however, remains unknown. Using a tissue-specific gene knockout approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 46 publications
1
25
0
Order By: Relevance
“…Global deletion of SHP-2 leads to early embryonic lethality [19,20], and induced SHP-2-deficient mice exhibit an osteopetrotic phenotype and generate much fewer osteoclasts [21]. The role of SHP-2 in osteoclastogenesis has been confirmed by a recent report showing that SHP-2 is required for multinucleated osteoclast formation by promoting preosteoclast fusion via the RANKL/NFATc1 signaling axis [11]. Wang et al generated monocyte/macrophagespecific SHP2 deficient mice and found that the mice exhibit mild osteopetrosis and their derived bone marrow macrophages have decreased osteoclast formation potential [22].…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Global deletion of SHP-2 leads to early embryonic lethality [19,20], and induced SHP-2-deficient mice exhibit an osteopetrotic phenotype and generate much fewer osteoclasts [21]. The role of SHP-2 in osteoclastogenesis has been confirmed by a recent report showing that SHP-2 is required for multinucleated osteoclast formation by promoting preosteoclast fusion via the RANKL/NFATc1 signaling axis [11]. Wang et al generated monocyte/macrophagespecific SHP2 deficient mice and found that the mice exhibit mild osteopetrosis and their derived bone marrow macrophages have decreased osteoclast formation potential [22].…”
Section: Discussionmentioning
confidence: 90%
“…However, previous studies have demonstrated that SHP-1 is a negative modulator of osteoclastogenesis, and mice lacking SHP-1 have increased number of osteoclasts [11,23,24]. Moreover, a recent study by Tang et al showed that SHP-1 inhibition repressed osteoblast differentiation and mineralization [25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Based on our findings that GA enhanced new bone formation, we investigated the osteogenic activity of GA using MG-63 cells. Osteoporosis is associated with osteoclast proliferation [61], and thus, bone loss was prevented by stimulating the process of osteoblast proliferation and suppressing the process of osteoclastogenesis in the OVX mice [62]. Osteoblast proliferation is regulated via binding to the ERE of the E 2 -ER complex and ERK activation [63,64].…”
Section: Discussionmentioning
confidence: 99%